Structural Determinants of School Discipline: Examining State-Level Racial Bias and Neighborhood Opportunity - Thompson, Erin L; Gonzalez, Marybel R; Scardamalia, Kristin M; Pham, Andy V; Adams, Ashley R; Gonzalez, Angelica; Rizzo Scarfone, Gabriella V; Lehman, Sarah M; Kaiver, Christine M; Hawes, Samuel W; Gonzalez, Raul (Journal of the American Academy of Child and Adolescent Psychiatry, 2025)
Addressing the disproportionate use of school detentions and suspensions among Black youth is crucial for reducing educational and health disparities across the life span. Yet, few studies have explored external factors beyond school or individual characteristics as potential contributors to school discipline disparities, such as state-level racial bias and neighborhood opportunity. A subsample from the larger Adolescent Brain Cognitive Development (ABCD) Study was used (n = 8,668; mean age at baseline = 9.5 years; 71% White; 29% Black). Anti-Black racial bias was measured using state-level indicators of racial prejudicial attitudes. Neighborhood opportunity was measured using census tract indicators within the education, health care, and social/economic domains. Logistic regression was used to examine risk of receiving a detention/suspension by the fourth wave of the study. Black youth had significantly higher detention/suspension rates than White youth, which could not be explained by teacher- or caregiver-reported externalizing concerns or by family characteristics. Social/economic indicators of neighborhood opportunity moderated the association between state-level racial bias and school discipline among Black youth, but not among White youth. Black youth living in states with greater racial bias were at higher risk for receiving school discipline when living in neighborhoods with more social/economic opportunities. In contrast, Black youth were at high risk for school discipline when living in neighborhoods with the lowest levels of opportunity regardless of state-level racial bias. Place-based characteristics appear to play a key role in explaining the inequitable use of school discipline among Black youth compared with White youth. This study used data from the Adolescent Brain Cognitive Development (ABCD) Study to explore why Black youth face higher rates of school discipline compared to White youth. Using data from 8,668 ABCD participants, the authors found that Black youth living in neighborhoods with more economic opportunities were more likely to be disciplined if they lived in states with higher racial bias. In contrast, Black youth living in neighborhoods with fewer opportunities faced high rates of discipline regardless of state racial bias. These findings suggest that both state and neighborhood factors, which are outside of a child's control, contribute to racial disparities in school discipline.